(untitled) (American Journal of Islam and Society, 2014)
This book is an interesting exposition of the reform discourse and reform ironies in the desert kingdom of Saudi Arabia ... a country ambivalent in its sense of security and insecurity, content in its presumed “orthodoxy,” uncertain about where it fits in this world and about its future, and unsure as to what extent it can continue to linger in its self-imposed cocoon – and yet, by the same token, how far it can go in opening up to a perceived threatening world. All of this ambivalence, as one senses while reading the book, hinders, obstructs, and consequently undermines King Abdullah’s alleged attempts at reform. In fact, as Hammond points out, many of these reforms have been nothing but “window dressing … driven entirely by the desire to protect the extraordinary powers of the Saudi royal family,” as well as by a felt necessity to appease the Americans (p. 150). Despite the king’s efforts to project the image of himself as a reformist, one “religious reform” (ṣaḥwah) figure describes him as simply being “out of the arena” (p. 137). Reforms, particularly judicial reforms, which Hammond describes as Abdullah’s “central plank,” are defined by a Najdi context as well as in Najdi terms (Najd is the central region of the Arabian Peninsula). The result has been a polity “trapped” within a pre-modern framework and ...